2019
DOI: 10.1103/physrevb.100.035438
|View full text |Cite
|
Sign up to set email alerts
|

Flexoelectricity as a universal mechanism for energy harvesting from crumpling of thin sheets

Abstract: Can the mere crumpling of a "paper" produce electricity? An inhomogeneous strain can induce electrical response in all dielectrics and not just piezoelectric materials. This phenomenon of flexoelectricity is rather modest unless unusually large strain gradients are present. In this work, we analyze the crumpling of thin elastic sheets and establish scaling laws for their electromechanical behavior to prove that an extremely strong flexoelectric response is achieved at sub-micron length-scales. Connecting with … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 45 publications
0
19
0
Order By: Relevance
“…Simplifying Equations (32) and 33, we get the governing equations of direct and converse effects as,…”
Section: Governing Equationsmentioning
confidence: 99%
See 1 more Smart Citation
“…Simplifying Equations (32) and 33, we get the governing equations of direct and converse effects as,…”
Section: Governing Equationsmentioning
confidence: 99%
“…the gradient of strain, is by having appropriate boundary and loading conditions. For this purpose, cantilever-shaped energy harvesters and sensors, due to the presence of nonuniform strain in bending, have been vastly investigated in the past [22][23][24][25][26][27][28][29][30][31][32][33] Variable mechanical characteristics can result in varying strain distribution within the domain. A few studies have suggested the use of special composite materials to achieve variation in mechanical properties and thereby a strain gradient [34][35][36][37][38][39].…”
Section: Introductionmentioning
confidence: 99%
“…introducing (38) in (39) in (42) and comparing the different terms of the resulting equation with (24), we obtain, after some calculations:…”
Section: Definition Of Effective Tensorsmentioning
confidence: 99%
“…Earlier works focused on exploiting flexoelectricity to design piezoelectric-like materials without using piezoelectrics [37,38]. A related notion is also of how flexoelectricity could mimic piezoelectricity [39].…”
Section: Introductionmentioning
confidence: 99%
“…Polymers show flexoelectric effect, and in recent years, the focus is on polyvinylidene fluoride (PVDF) that shows the strongest effect and is applied in many applications like energy harvesting, 5–9 implantations, 10 structural components, 11 soft robots, 12 protecting coatings 13 for steel structural members, flexible pipelines 14 as multilayer structures for the transport of oil and gas in offshore oil and gas fields, nano‐generators, 15 and sensors 16 . Finally, PVDF flexoelectricity plays an important role in applications requiring soft membranes 17 …”
Section: Introductionmentioning
confidence: 99%